Moving out: End-of-life decisions at a geriatric affordable housing facility in Brooklyn, NY - O'Hare, Brian J. (The Australian journal of anthropology, 2018)
This article will focus on perceptions about the health of tenants at an independent-living residence for indigent elderly and disabled people. At this site tenants often resisted aid provided, which was a marked contrast to their caregiver's moral and legal imperative to help. This “caregiver's dilemma” will be explored within the shifting perspectives of older adults with low social and economic positions. In this diverse setting social workers engaged in caregiving practices to address social and economic inequalities. Ultimately, regulations designed to alleviate inequality created a framework to judge tenants on multiple fronts to foster and maintain their wellbeing. Under these conditions, interpretations of tenants’ behaviours toward care practices created boundaries with tensions embroiled in larger issues surrounding ethnic, linguistic, and social difference. By exploring these boundaries this research aims to address the growing complexity of affordable housing in the United States as the population-at-large continues to diversify.